Large osteochondroma excision from distal radius - Modi, Lomesh P.; Katkani, Anmol; Tomar, Aman; Gupta, Vatsal A.; Desai, Sarvang (International Journal of Research in Orthopaedics, 2025)
Osteochondroma is a common benign bone tumor, originating within the periosteum as a small cartilaginous nodule. The distal femur, the proximal tibia, and the proximal humerus are the most common locations and the majority of these lesions cause no symptoms and are discovered incidentally. We present a rare solitary large (approx. 11 cm long) osteochondroma originating from the ventral aspect of the distal end of the radius with mechanical restriction of movement of the wrist joint in an 8-year-old female patient. The biopsy is suggestive of benign chondro-osseous neoplasm favoring the diagnosis of osteochondroma. Surgical intervention with the excision of the osteochondroma of the distal radius was performed and thereby the symptoms showed a complete resolution.